Experiences of creating digital content for teaching and learning through working in staff-student partnerships - Gregory-Ellis, Charlotte (International Journal for Students as Partners, 2022)
Most staff-student partnerships are carried out between students who are studying on the course the academics are teaching; this study is different in showing how skilled students work in partnership with academic staff across the university to create digital content for teaching. The students work as digital media producers (DMPs) within the institution, delivering expertise in the creation of digital content working alongside the academics who develop the subject content. This qualitative study had a small, purposive, and selected sample. Academics and the DMPs undertook focus groups to gather insights into their experiences of transforming teaching and learning into a collaborative process. Thematic data analysis and coding were utilised to generate themes, with consideration to the research objectives while analysing the transcripts. Themes appeared, such as having a central support to encourage relationships and build upon skillsets, thereby supplying the students with an authentic experience and aiding their future employment prospects.